2009
DOI: 10.1111/j.1365-2966.2008.14287.x
|View full text |Cite
|
Sign up to set email alerts
|

On the aberration-retardation effects in pulsars

Abstract: The magnetospheric locations of pulsar radio emission region are not well known. The actual form of the so-called radius-to-frequency mapping should be reflected in the aberrationretardation (A/R) effects that shift and/or delay the photons depending on the emission height in the magnetosphere. Recent studies suggest that in a handful of pulsars the A/R effect can be discerned with respect to the peak of the central core emission region. To verify these effects in an ensemble of pulsars, we launched a project … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 27 publications
7
32
0
1
Order By: Relevance
“…Several observational evidence suggest that the radio emission arises around 500 kilometers above the neutron star due to coherent curvature radiation (Mitra & Rankin 2002;Kijak & Gil 2003;Mitra & Li 2004;Krzeszowski et al 2009;Mitra et al 2009). These basic observational features can be best explained by the so called steady state polar cap models (e.g., Sturrock 1971;Ruderman & Sutherland 1975).…”
Section: Physical Implications Of Nullingmentioning
confidence: 99%
“…Several observational evidence suggest that the radio emission arises around 500 kilometers above the neutron star due to coherent curvature radiation (Mitra & Rankin 2002;Kijak & Gil 2003;Mitra & Li 2004;Krzeszowski et al 2009;Mitra et al 2009). These basic observational features can be best explained by the so called steady state polar cap models (e.g., Sturrock 1971;Ruderman & Sutherland 1975).…”
Section: Physical Implications Of Nullingmentioning
confidence: 99%
“…Gangadhara & Gupta (2001, hereafter GG01), noted that profiles of selected pulsars have outer cones more shifted towards early phase than inner cones. Krzeszowski et al (2009) find at least a tendency towards this effect in most pulsars in their sample, but they also find some counterexamples (e.g. B1831−04).…”
Section: Pulsars With Phase‐shifted Conesmentioning
confidence: 80%
“…But the retardation phase shift was ignored in BCW91, as they assumed a constant emission height across the pulse. In GG01, GG03, Johnston & Weisberg (2006) and Krzeszowski et al (2009) it was shown though that the emission altitude is not constant across the pulse, and hence retardation has to be taken into account while estimating the A/R phase shifts. Further, showed that the centroid of the intensity profile advances by ∼2 r/r LC while the PPAIP is delayed by ∼2 r/r LC due to A/R effects with respect to the meridional plane.…”
Section: Methods For Estimating the Absolute Emission Heightsmentioning
confidence: 99%
“…The results of this purely geometric method are found to be in rough agreement with those of BCW91. However, the relativistic phase shift method clearly indicates that the emission altitude across the pulse window is not constant (GG01; GG03; DRH04; Johnston & Weisberg 2006;Krzeszowski et al 2009). …”
Section: Introductionmentioning
confidence: 99%